2019
DOI: 10.1051/matecconf/201925903006
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Public Transport Accessibility for Elderly

Abstract: The growth acceleration in the older population has been observed in many countries which creates a significant challenge to transportation. Public transport is an essential component of most people’s lives. This specific group of population growth will require special attention to accessibility and mobility issues in combination with the transport system which undoubtedly can play a key role to support ageing. Good health, quality of life and independence are fundamental values for the life as well as mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The elderly population and time-based index [71][72][73] A recent study introduced elderly time-based accessibility.…”
Section: Index Definition Highlightsmentioning
confidence: 99%
“…The elderly population and time-based index [71][72][73] A recent study introduced elderly time-based accessibility.…”
Section: Index Definition Highlightsmentioning
confidence: 99%
“…The study also found that the likelihood of the motorcyclists to choose bus riding increase by 85.4% if the trip duration by bus reduces [14]. A comparable situation has been seen in a few other nations such as Japan [2] and Australia [19], albeit mostly in rural regions. These accessibility and reliability difficulties should be addressed in accord with promoting active ageing and more sustainable transport use among the older adults [20].…”
Section: Discussionmentioning
confidence: 70%
“…However, education and recreation centres have better coverage in all Melbourne SA1s (Figures 3-5). A substantial portion (8%) of the total travel of the elderly involves education escort, specifically for primary school children [50,52]. As primary schools are zoned, children are most likely to attend primary school in the area where they live.…”
Section: Resultsmentioning
confidence: 99%
“…According to VISTA [50], older people mostly travel to four main categories of POIs: (1) shopping centres, (2) healthcare centres, (3) education centres, and (4) recreational centres [52]. Hence, these four most-travelled POI categories by the elderly were considered for the calculation of the index in this study.…”
Section: Index and References Definition Highlightsmentioning
confidence: 99%